Constitutional Education for Karang Taruna Youth on Rights and Obligations of Citizens - Risman Setiawan (Yayasan Cerdas Pedia Indonesia, 2026)
This initiative sought to improve constitutional awareness among Karang Taruna youth in Kendari City by deepening their understanding of citizens’ rights and obligations. It responded to weak constitutional literacy and growing civic apathy among young people. The program applied an educational and persuasive method through interactive lectures, group discussions, and pre-test and post-test assessments. The results showed a notable improvement in civic knowledge, with average comprehension scores increasing by more than 45 percent across indicators of constitutional rights and obligations. The activity helped internalize national values and build a more positive orientation toward citizenship. These findings indicate that structured non-formal education can strengthen legal awareness and social character among digital native youth. The policy implication emphasizes the need to position Karang Taruna as a strategic local government partner in sustaining constitutional literacy and national stability. Practically, this initiative offers an adaptive legal education model for youth organizations at the level.